2016
DOI: 10.12816/0033775
|View full text |Cite
|
Sign up to set email alerts
|

The Fibrinogen / CRP Ratio as a New Parameter for the Prediction of Disseminated Intravascular Coagulation in Patients with HELLP Syndrome

Abstract: Background: The syndrome of Hemolysis, elevated Liver enzymes, and Low Platelet count (HELLP) is a life-threatening variant of preeclampsia, and may be accompanied by disseminated intravascular coagulation (DIC). Recently the fibrinogen/C-reactive protein (CRP) ratio has been suggested as a measurement that predicts onset of DIC. The authors sought to analyze the fibrinogen/CRP ratio among obstetric patients who developed DIC due to HELLP syndrome. Aim: the aim of this study is to determine if the fibrinogen/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(16 reference statements)
1
0
0
Order By: Relevance
“…The DIC rate was substantially higher than those with CRP level >100 mg/dl among patients with acute leukemia (Ji, 2015). These findings are consistent with Tamara and colleagues (2016), who suggested that CRP levels were high in Overt DIC patients among HELLP syndrome, which is a complication of pregnancy characterized by hemolysis, elevated liver enzymes, and a low platelet count. The CRP levels cut–off point of >100 mg/dl increased Overt DIC’s predictive value.…”
Section: Discussionsupporting
confidence: 92%
“…The DIC rate was substantially higher than those with CRP level >100 mg/dl among patients with acute leukemia (Ji, 2015). These findings are consistent with Tamara and colleagues (2016), who suggested that CRP levels were high in Overt DIC patients among HELLP syndrome, which is a complication of pregnancy characterized by hemolysis, elevated liver enzymes, and a low platelet count. The CRP levels cut–off point of >100 mg/dl increased Overt DIC’s predictive value.…”
Section: Discussionsupporting
confidence: 92%